Baliak ka Surau: an Action Research to Empower Masjid to Learn Islamic Science in Kampuang Sarugo - Candra Gunawan; Abdi Aldila Putra; Raihan Shidqi Ra’uf; Yasirli; Vedrand Gilang Wahyudi Haris (ASSUNNAH PRESS, 2023)
This KKNT activity aims to enlighten the public about the importance of mosques for Muslims and how to empower mosques as centers of Islamic community activities, especially as a means for tafaqquh (understanding) Islamic sciences. The method used in this community service activity is Participatory Action Research. Sarugo Village, Nagari Koto Tinggi, Gunuang Omeh District, Fifty Cities District, West Sumatra is the target of this year's STAI As-Sunnah KKNT activities. This place was chosen because, based on observations and interviews conducted with the people in the area, it was concluded that there were several mosques, but the number of Muslim people who had the awareness to prosper the mosques with worship activities was very minimal, this was due to the absence of preachers who provided enlightenment to the public about the importance of mosques for Muslims, and how to empower mosques as centers of Islamic community activities. KKNT activities are carried out for two weeks, from March 25 to April 9, 2023. The forms of activities carried out to achieve the above objectives are conducting Islamic study activities at mosques, reviving the role of mosque youth, visiting local communities at mosques by holding positive activities such as cooperation in mosques, breaking the fast together, and sticking up posters of Islamic knowledge, such as posters for ablution prayers, prayer posters for entering mosques, and so on. It was concluded that through these activities, Kampuang Sarugo's enthusiasm increased to come to worship at the Masjid and prosper the Masjid through other positive activities.